Rapid photocatalytic degradation of cationic organic dyes using Li-doped Ni/NiO nanocomposites and their electrochemical performance. (23rd December 2020) - Ranjitha, R.; Meghana, K. N.; Kumar, V. G. Dileep; Bhatt, Aarti S.; Jayanna, B. K.; Ravikumar, C. R.; Santosh, Mysore Sridhar; Madhyastha, H.; Sakai, K.
Abstract : This work reports novel bi-functional Li-doped Ni/NiO nanocomposites as potential candidates for energy storage and water treatment applications. Abstract : Metal/metal oxide nanocomposites (NCs) have been attracting significant attention in recent times because of their applications in the fields of energy and environment. In the present work, we investigate the photocatalytic and electrochemical performances of Ni/NiO NCs synthesized by a facile and cost-effective reduction method using lithium salt as the dopant. Lithium influences the size, morphology and structural constitution of the final product. A variation in the lithium percentage was seen to have a direct effect on the Ni content. The structural conformation of the samples has been analyzed by XRD and further confirmed by XPS. A low optical energy bandgap (∼3.7 eV) and a mesoporous structure of the as-prepared samples were seen to play a crucial role in achieving the photocatalytic degradation of the cationic organic dyes concomitant to its electrochemical activity. On illumination with UV light, the Li-doped Ni/NiO NCs demonstrated rapid degradation of crystal violet and methyl violet 2B dyes. The synergism arising due to the substitutional doping of lithium and the presence of metallic nickel leads to efficient photodegradation of the dye pollutants by the catalysts. Further, the Li-doped Ni/NiO NCs displayed a better electrochemical performance than the undoped samples. The NC with 1 wt% Li exhibited the best values of specific capacitance (276.2 F g −1 at 5 A g −1 ) with an excellent cycling ability (<1% capacitance loss after 2000 cycles). The enhanced electrochemical and photocatalytic results suggest the dual activity of these nanocomposites in energy storage and water treatment applications.